2005
DOI: 10.1109/tip.2005.852196
|View full text |Cite
|
Sign up to set email alerts
|

Salt-and-pepper noise removal by median-type noise detectors and detail-preserving regularization

Abstract: Abstract-This paper proposes a two-phase scheme for removing salt-and-pepper impulse noise. In the first phase, an adaptive median filter is used to identify pixels which are likely to be contaminated by noise (noise candidates). In the second phase, the image is restored using a specialized regularization method that applies only to those selected noise candidates. In terms of edge preservation and noise suppression, our restored images show a significant improvement compared to those restored by using just n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
539
0
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 947 publications
(584 citation statements)
references
References 20 publications
1
539
0
11
Order By: Relevance
“…This is an attempt in direction where huge legacy of developed digital image processing methods can be used for a different purpose with respect to the original one. Raymond H.Chan et all., [14]In this paper, we propose a powerful two-stage scheme which combines the variational method proposed with the adaptive median filter [5]. More precisely, the noise candidates are first identified by the adaptive median filter, and then these noise candidates are selectively restored using an objective function with an data-fidelity term and an edgepreserving regularization term.…”
Section: International Journal For Research In Applied Science and Engimentioning
confidence: 99%
“…This is an attempt in direction where huge legacy of developed digital image processing methods can be used for a different purpose with respect to the original one. Raymond H.Chan et all., [14]In this paper, we propose a powerful two-stage scheme which combines the variational method proposed with the adaptive median filter [5]. More precisely, the noise candidates are first identified by the adaptive median filter, and then these noise candidates are selectively restored using an objective function with an data-fidelity term and an edgepreserving regularization term.…”
Section: International Journal For Research In Applied Science and Engimentioning
confidence: 99%
“…A critical parameter was the SAM maximum angle field, to define which pixel may (or may not) be classified as OOMW areas. Based on the spectral profiles from in-situ observations [34], it was found that OOMW disposal areas tend to have low reflectance values in the visible part of the spectrum (ρ < 5%) and relative high reflectance values in the near infrared part of the spectrum (ρ = 10%). Thus, a minimum SAM angle was decided using these thresholds.…”
Section: Case Study 1: Mesaras Inletmentioning
confidence: 99%
“…This noise appears owing to the presence of minute grey scale variations within the image. Median filtering could be a widespread technique of the image improvement for removing noise without effectively reducing the image sharpness [10].…”
Section: Types Of Filters 41 Median Filtermentioning
confidence: 99%